Whole Transcriptome Sequencing Analyses Reveal Molecular Markers of Blood Pressure Response to Thiazide Diuretics. Issue 1 (December 2017) - Sá, Ana; Webb, Amy; Gong, Yan; McDonough, Caitrin; Datta, Somnath; Langaee, Taimour; Turner, Stephen; Beitelshees, Amber; Chapman, Arlene; Boerwinkle, Eric; Gums, John; Scherer, Steven; et al.
Abstract Thiazide diuretics (TD) are commonly prescribed anti-hypertensives worldwide. However, <40% of patients treated with thiazide monotherapy achieve BP control. This study uses whole transcriptome sequencing to identify novel molecular markers associated with BP response to TD. We assessed global RNA expression levels in whole blood samples from 150 participants, representing patients in the upper and lower quartile of BP response to TD from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) (50 whites) and from PEAR-2 (50 whites and 50 blacks). In each study cohort, we performed poly-A RNA-sequencing in baseline samples from 25 responders and 25 non-responders to hydrochlorothiazide (HCTZ) or chlorthalidone. At FDR adjusted p-value < 0.05, 29 genes were differentially expressed in relation to HCTZ or chlorthalidone BP response in whites. For each differentially expressed gene, replication was attempted in the alternate white group and PEAR-2 blacks.CEBPD (meta-analysis p = 1.8 × 10−11 ) andTSC22D3 (p = 1.9 × 10−9 ) were differentially expressed in all 3 cohorts, and explain, in aggregate, 21.9% of response variability to TD. This is the first report of the use of transcriptome-wide sequencing data to identify molecular markers of antihypertensive drug response. These findings supportCEBPD andTSC22D3 as potential biomarkers of BP response to TD.